Analysis of potential genes for the development of potatoes (Solanum tuberosum) with heat stress-tolerance - Bernadetta Rina Hastilestari (Nusantara Science and Technology Proceedings, 2021)
Potato (Solanum tuberosum) is a widely cultivated plant in the highlands. Low temperature, such as temperature at night, is required for tuber formation. However, global warming has increased global temperature and causing a decrease in crop yields. To meet the growing demand for potatoes, the planting area needs to be expanded. Planting can be done at the medium-altitude or even lowland by developing potato varieties that are well-adapted to a higher temperature. The first step to achieve this goal is to analyze the potential genes for potato breeding by comparing the data from the microarray. Genes related to heat shock proteins affect the resistance of potato plants towards the increasing temperatures in the environment.